The use of Slovak Simmental breed in suckler beef system - Vavrišínová, Klára; Hozáková, Katarína; Juhás, Peter; Janíček, Martin; Margetín, Milan; Obtulovič, Peter (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
The aim of this study was to monitor productive characteristics of Slovak Simmental breed and crossbreeds of different proportion (>50% of Slovak Simmental breed) in the system of suckling beef in Slovakia. Study evaluated a total of 932 animals for growth parameters and 75 animals for carcass characteristics. Analysing of calving ease showed 4.95% proportion of calving with assistance (calving ease score 2 from 4 point scale). These were found in calving of one gender – heifers. All other recorded calving was without need of assistance. Analysis of variance confirmed highly significant influence of the sire on calving difficulty (P<0.001) and significant impact of the sex and birth season as well (P<0.01). Higher live weight at birth was determined in bulls (32.90 kg vs. 31.13 kg). Similarly, analysis of variance of the birth weight verified highly significant influence of the sire (P<0.001). In monitored herds, cows calved throughout the year, with highest percentage of calving in winter season (from January to March) – 36.5%. On the other hand, fewer cows calved in the season between July and September (4.99%). The highest average live weight at 120 days according to the calving season was determined in calves born in February (216.78 kg). Within evaluation of impact of the calving season on growth characteristics, highly significant influence on the birth weight (P<0.001) and significant influence on weaning weight (P<0.05) were determined. Average dressing percentage of bulls was 54.97%; the highest number of slaughtered bulls (70%) was designated in commercial class E/2 and U/2.